2015
DOI: 10.1007/s11085-015-9581-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Vapor on the Oxidation Behavior of Alumina Forming Austenitic Stainless Steels

Abstract: The isothermal oxidation behavior of three alumina forming austenitic (AFA) stainless steels with varying composition was studied at 650 and 800°C in dry air and gases which contained water vapor. The AFA alloys exhibited better oxidation resistance than a ''good chromia former'' at 650°C, particularly in H 2 Ocontaining atmospheres by virtue of alumina-scale formation. Although the AFA alloys were more resistant than chromia formers, their oxidation resistance was degraded at 650°C in the presence of water va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Due to relatively high creep strength and good corrosion resistance, austenitic stainless steels are currently used widely in ultra-supercritical units. Up to now, many researchers studied oxidation characteristics in high-temperature steam environment of austenitic stainless steels [3][4][5][6][7][8][9][10][11][12][13][14]. Typical austenitic steels form nominally two-layered scales under steam conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to relatively high creep strength and good corrosion resistance, austenitic stainless steels are currently used widely in ultra-supercritical units. Up to now, many researchers studied oxidation characteristics in high-temperature steam environment of austenitic stainless steels [3][4][5][6][7][8][9][10][11][12][13][14]. Typical austenitic steels form nominally two-layered scales under steam conditions.…”
Section: Introductionmentioning
confidence: 99%
“…And it was found that the higher the water vapor content, the worse the oxidation resistance. N. M. Yanar et al [ 23 ] found that OC4 steel had better oxidation resistance in 3% water vapour than in 10% at 800 °C. This explains that OC4 steel can form a continuous alumina protective scale in a 3% water vapour environment but has internal oxidation in 10% water vapour.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…Many previous studies [11][12][13] have shown that one of the most effective ways to enhance wear resistance and surface hardness is by coating it. Coating technology can be broadly categorised into two groups: one is thermal diffusion type, including gas diffusion infiltration, hot dip coating, packcementation, 13 and high-energy beam surface treatment 14,15 ; the other is deposition type, including physical vapour deposition, [16][17][18][19] chemical vapour deposition, [20][21][22] electroplating, 23,24 spraying, 25,26 micro-arc oxidation, 27,28 etc. Pack-cementation is an efficient, simple, mature, and low-cost approach for preparing metallic and ceramic coatings on metals and alloys.…”
Section: Introductionmentioning
confidence: 99%